The Cinema Consumption Style and Its Relationship with Cinema Literacy among Ilam University Students - asghar mirfardi; abdollah valinezhad; Ehsan Khanmohamadi (توسعه اجتماعی, 2020)
The cinema and cinema consumption is one of cultural consumption of each society. This paper aimed to evaluate the cinema consumption style among men and women students and its relation with cinema literacy and knowledge. Using survey method, population of the study has been Ilam university students, from which 400 students were determined, based on Lin Sampling Table (1976) as the sample size and were selected by classified-multi stage random sampling method. A mixed self-administrated and standard questionnaire was used as the research instrument for data collection, in which face validity and Cronbach's alpha used for its validity and reliability, respectively. The findings showed that there is significant direct and moderately strong correlation between cinema literacy and knowledge, from one side, and cinema consumption, from another side. Totally, study showed that cinema consumption is transforming via following cinema literacy and knowledge.